Atypical Femur Fracture in a Teenager on Chronic Imatinib Therapy - Ana C. Belzarena; James L. Cook (Case Reports in Oncological Medicine)
Atypical femoral fractures (AFFs) are rare fractures usually associated with medications that can ultimately alter bone metabolism. Imatinib, a drug prescribed for treatment of chronic myeloid leukemia (CML), has been associated with altered bone homeostasis, however, with unknown clinical significance. Here, we present the case of a 17-year-old female, with a diagnosis of CML undergoing chronic imatinib therapy, who developed an AFF treated successfully with prophylactic fixation with intramedullary nailing. Our case underscores the importance of prompt recognition of this entity to allow patients timely appropriate care, even at an early age.